2016
DOI: 10.18517/ijaseit.6.2.749
|View full text |Cite
|
Sign up to set email alerts
|

Selected Macronutrient Uptake by Sweet Corn under Different Rates of Liquid Organic Fertilizer in Closed Agriculture System

Abstract: In the last few years, soil deterioration due to excessive application of synthetic agrochemical has become growing concern. Use of organic fertilizer is believed to be able to enhance soil quality. The objective of this experiment was to determine nitrogen, phosphorus, and potassium uptakes by sweet corn as affected by local based liquid organic fertilizer (LOF) under closed agriculture system. The experiment was conducted in Closed Agriculture Production System (CAPS) Research Station in Air Duku Village, Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
2
17
0
4
Order By: Relevance
“…The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients. This was confirmed by our previous result [12], [13], [14] where tithonia-enriched liquid organic fertilizer contained 3,36% N, 146 ppm P, and 0.033% K. Although nitrogen content of this liquid organic fertilizer somehow comply with the standard quality for organic fertilizer issued by Indonesian Standardization Board (SNI 19-7030-2004) where total N should be > 0.4 %, but P and K content were very much lower than standard (SNI-19-7030-2004) which must be above 0.10% (P 2 O 5 ) and 0.20% (K 2 O), respectively.…”
Section: J C/nsupporting
confidence: 90%
See 2 more Smart Citations
“…The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients. This was confirmed by our previous result [12], [13], [14] where tithonia-enriched liquid organic fertilizer contained 3,36% N, 146 ppm P, and 0.033% K. Although nitrogen content of this liquid organic fertilizer somehow comply with the standard quality for organic fertilizer issued by Indonesian Standardization Board (SNI 19-7030-2004) where total N should be > 0.4 %, but P and K content were very much lower than standard (SNI-19-7030-2004) which must be above 0.10% (P 2 O 5 ) and 0.20% (K 2 O), respectively.…”
Section: J C/nsupporting
confidence: 90%
“…The source of green biomass should be a combination of several green biomasses in order to produce liquid organic fertilizer with high N, P, K, Ca, and Mg content. In addition, it also important to mixture the green biomasses with other natural composting material, such as poor soil [36], wood ash [37], cow manure [12], [13], [14], [38] in order to increase composting rates, nutrient quality and crop yields. The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients.…”
Section: J C/nmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of green biomass should be a combination of several green biomasses in order to produce liquid organic fertilizer with high N, P, K, Ca, and Mg content. In addition, it also important to mixture the green biomasses with other natural composting material, such as poor soil [36], wood ash [37], cow manure [12], [13], [14], [38] in order to increase composting rates, nutrient quality and crop yields. The use of a single green biomass for liquid organic fertilizer might provide high particular nutrient content, but low in other nutrients.…”
Section: J C/nmentioning
confidence: 99%
“…The use of liquid organic fertilizers has been widely practiced for organic vegetable production. Although some publications reported that effects of liquid organic fertilizer had been successfully improved growth and yield of many vegetables, such as in lettuce [5], green cabbage [6], cauliflower [7], kaelan [8], potato [9], tomato [10] and sweet-corn [11], the use of tithonia-enriched liquid organic fertilizer in organic vegetable production have been found to be less effective in promoting growth and yield of carrot [12] and sweet corn [13], [14]. Green biomass is one of the main components to determine the effectiveness of liquid organic fertilizer for vegetable production.…”
Section: Introductionmentioning
confidence: 99%